Penggunaan Metode Baby Signs terhadap Kemampuan Berbicara Anak Usia 2 Tahun: Kajian Psikolinguistik - Nur Oktaviana Dewi; Hendra Setiawan (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research article aims to find out how the Baby Signs method is used, and to describe the results of using this method on the speaking ability of 2 years old children. The use of the Baby Signs method aims to produce a fun learning process for children. So, children will easily learn to recognize words and speak. Previously, the researcher calculated in advance the child's language acquisition, with using Brown's MLU Theory. Language acquisition is the subject of psycholinguistics. In this study, the researcher conducted descriptive qualitative research using the SSR (single subject research) method and collected data through observation and interviews. While the next technique is the recording and recording technique. The results of using the Baby Signs method in the process of learning to speak for children aged 2 years can be said to be successful, because children become more enthusiastic in learning to speak, focus more when being spoken to, train articulation determination, synchronize using pressure and tone, as well as perfect word choice. In the MLU calculation, the subject is already in stage II, namely (1.5-2.0) words in speech, at the age of 22-28 months. Meanwhile, if based on age the subject is 2 years or 24 months. So there is no problem of speech delay that he experienced.